Discrete-element modelling of the trapdoor arching effect in sand and rubberised sand. Issue 6 (11th December 2020) - Khatami, Hamidreza; Deng, An; Jaksa, Mark
Abstract : The onset and evolution of soil arching in a trapdoor apparatus was investigated using discrete-element modelling (DEM). The effects of wall friction, particle size and material type (sand and rubber–sand) on the micro-behaviour of the granular material during arching was monitored. It was observed that when the particles are large with respect to the trapdoor width, they form a stable arch over the trapdoor element. An 'intermediate zone' within the granular materials is then introduced. This is the zone where inter-particle contact forces increase in the early stage of active arching and then decrease as the trapdoor displacement continues. The DEM simulation results showed that the granular particles rearranged in reaction to arching, causing uneven densities throughout the backfills. The distributions of two-dimensional stresses in the cross-section of the modelled sand and rubber–sand backfills were obtained using the kriging method and compared.